Analisis Integrasi Keterampilan Abad 21 Dalam Buku Teks Ekonomi Kelas XII SMA/MA - Nisa', Riska Khoirun; Herlindawati, Dwi; Suharso, Pudjo (Jurnal Pendidikan Akuntansi (JPAK), 2024)
This study aims to analyze the presence of 21st century skills in Economics textbooks used in class XII SMA/MA learning activities. This is based on the important role of textbooks used as learning resources that help prepare students to become highly competitive and qualified individuals to face global challenges. The analysis in this study focused on four indicators of 21st century skills, namely critical thinking skills, creative thinking skills, communication skills, and collaboration skills. This research included quantitative research using a descriptive approach with the documentation method. This study used descriptive statistical analysis techniques with percentage techniques. This study obtained results showing that the Economics textbook for class XII SMA/MA published by Grafindo Media Pratama in 2019 was considered to integrate 21st century skills with a percentage of communication skills of 100% with very good criteria, collaboration skills of 100% with very good criteria, creative thinking skills of 83.5% with very good criteria and critical thinking skills of 75% with good criteria. This study recommends schools to provide more varied learning resources that can support students to practice 21st century skills and recommends teachers to use the learning model.